2024
DOI: 10.1210/clinem/dgae087
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolactin Levels and Mortality in Adults Without Prolactinoma: A Meta-Analysis

Andreas S Papazoglou,
Ana Rita Leite,
Dimitrios V Moysidis
et al.

Abstract: Purpose Prolactin is a highly versatile, multifunctional hormone synthesized and secreted by lactotroph cells of the anterior pituitary. Its metabolic role has been extensively studied even in normoprolactinemic populations. Recently, a wealth of observational data outlines the potential prognostic value of prolactin in various clinical settings. This systematic review aims to systematically evaluate and quantitatively synthesize the association between serum prolactin levels and risk of mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In addition, prolactin receptor expression appears to be linked to myocardial hypertrophy [46]. Although prolactin did not reliably reflect cardiometabolic risk in an analysis of 3232 subjects from the Framingham Heart Study [47], a recent study of 10,907 patients with type 2 diabetes showed a positive association of serum prolactin with mortality [48], and a recent meta-analysis of 14 studies involving 23,596 patients confirmed that serum prolactin is an independent predictor of all-cause mortality and cardiovascular mortality [49]. The results of our experiment correlated well with these data from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prolactin receptor expression appears to be linked to myocardial hypertrophy [46]. Although prolactin did not reliably reflect cardiometabolic risk in an analysis of 3232 subjects from the Framingham Heart Study [47], a recent study of 10,907 patients with type 2 diabetes showed a positive association of serum prolactin with mortality [48], and a recent meta-analysis of 14 studies involving 23,596 patients confirmed that serum prolactin is an independent predictor of all-cause mortality and cardiovascular mortality [49]. The results of our experiment correlated well with these data from the literature.…”
Section: Discussionmentioning
confidence: 99%